Determination of the Astrophysical S-factor and Thermonuclear Reaction Rates of the (α,n) Medium Elements Reactions - Mohammed Issa Hussein; Ramadhan Hayder Abdullah (Zanco Journal of Pure and Applied Sciences, 2020)
Cross-sections of the (α,n) medium elements reactions as a function of energies of alpha (α)-particle such as 45Sc(α,n)48V , 48Ti(α,n)51Cr , 51V(α,n)54Mn , 50Cr(α,n)53Fe , 55Mn(α,n)58Co , 54Fe(α,n)57Ni , 59Co(α,n)62Cu , 62Ni(α,n)65Zn , 63Cu(α,n)66Ga , and 66Zn(α,n)69Ge have been interpolated from threshold to 10 MeV in step of 0.05 MeV by using the Program of MATLAB. Weighted averages of the Cross-sections in (mb) have been utilized to calculate the astrophysical S-factor and thermonuclear reaction rates as a function of the energy of the center of mass, Ec.m. and T9 Which is the temperature in units of 10 9K (T9 = 10-9 T) respectively. Polynomial relationships have been utilized to fit the computed astrophysical S-factor and thermonuclear reaction rates to determine the astrophysical S-factor at various Ec.m. and thermonuclear reaction rates at various T9 from best fitting equations with the minimum Chi-Square. Empirical formulae of set of reactions 45Sc(α,n)48V , 48Ti(α,n)51Cr , 51V(α,n)54Mn , 55Mn(α,n)58Co , 59Co(α,n)62Cu , and 45Sc(α,n)48V , 48Ti(α,n)51Cr , 51V(α,n)54Mn , 55Mn(α,n)58Co , 62Ni(α,n)65Zn , 66Zn(α,n)69Ge have been utilized to compute astrophysical S-factor as a function of Ec.m. and Z and thermonuclear reaction rates as a function of T9 and the target nucleus atomic number Z. The results have been compared with the embraced astrophysical S-factor and thermonuclear reaction rates that have been calculated from the fitting equations which have a good agreement.